Effect of conservation methods on the bioaccessibility of bioelements from in vitro‐digested edible mushrooms - Kała, Katarzyna; Krakowska, Agata; Zięba, Piotr; Opoka, Włodzimierz; Muszyńska, Bożena (Journal of the science of food and agriculture, 2021)
BACKGROUND The release of bioelements from edible mushrooms (Agaricus bisporus, Cantharellus cibarius, and Imleria badia) was examined using in vitro simulated gastrointestinal digestion to assess their health‐promoting potential. The following samples were tested: fresh, frozen, dried in a food dryer, dried in the sun, and lyophilized. The samples were incubated in gastric juice (pepsin, NaCl, HCl) and in intestinal juice (NaHCO3, pancreatin, bile salts) with the aim of verifying the bioaccessibility of the bioelements and the digestibility of mushrooms. Four bioelements that are essential for the human body were studied: Mg, Zn, Cu, and Fe. RESULTS It was found that Mg was extracted in the highest amounts from the sun‐dried A. bisporus (1.620 g kg−1 d.w.). In the case of microelements, the lyophilized fruiting bodies of I. badia released Zn in the highest quantities (0.180 g kg−1 d.w.). Lyophilization and sun‐drying methods were more advantageous than other methods. Fresh material was a more valuable source of bioelements than frozen material. CONCLUSION Our results showed that edible mushrooms have a high content of bioelements that are easily bioaccessible, which indicates their health‐promoting properties. © 2020 Society of Chemical Industry